Self-Harming and Sense of Agency in Patients With Borderline Personality Disorder - Colle, Livia; Hilviu, Dize; Rossi, Roberta; Garbarini, Francesca; Fossataro, Carlotta (Frontiers in Psychiatry, 2020)
Self-harm is considered a pervasive problem in several psychopathologies, and especially in Borderline Personality Disorder (BPD). Self-harming behaviours may be enacted for many purposes for example to regulate emotions and to reduce dissociation. BPD patients often report dissociative episodes, which may be related to an altered body awareness, and in particular to an altered awareness of the sense of agency. The sense of agency draws in part upon perceptions of being in control of our bodies and our physical movements, of being able to act upon environments. In this study, we aim to investigate whether dissociative experiences of BPD patients may be linked to an altered sense of agency and whether self-injurious actions may, through strong sensorial stimulation, constitute a coping strategy for the reduction of the distress associated with these dissociative experiences. A group of 20 BPD patients, of whom 9 presented self-harming behaviours, took part in the study and were compared with an age-matched control group of 20 healthy individuals. Sense of agency was evaluated through the Sensory Attenuation paradigm. In this paradigm, in a comparison with externally generated sensations, the degree to which perceived intensity of self-generated sensations is reduced is considered an implicit measure of sense of agency. As we expected, we found a significant difference in the perceptions of the two groups. The attenuation effect appeared to be absent in the BPD group while it was present in the control group. However, further analysis revealed that those BPD patients who engaged in self-harming behaviours presented a degree of attenuation which was similar to that of the control group. These results confirm the hypothesis that self-injurious actions constitute a coping strategy for increasing the sense of agency. We finally discuss the correlation of these experimental results with some clinical self-evaluation measures assessing dissociation, anxiety, depression, and affective dysregulation.